Understanding Halal For Traders In The Raden Fatah State Islamic University, Palembang - Nilawati Nilawati; Rudi Aryanto; Nurhalifa Nurhalifa (UNIVED Press, 2025)
It's crucial to discuss food and drink in daily life. The aforementioned food and beverage must meet the requirements set down by sharia, which include being pure, beneficial, and harm-free. Thus, it is crucial for traders to comprehend this in the food and beverage industry. This study discovered that, out of 51 samples of respondents, 25 food and drink vendors at the Sudirman Campus setting of the Raden Fatah State Islamic University of Palembang did not comprehend halallan thayyiban, while 13 traders did. Even so, the majority of them were just aware of what halal meant; they had no idea what thayyiban meant. Compared to food and beverages that are purchased already prepared and then resold, processing food to meet halal and thayyib regulations requires more capital. So that providing for a resilient family's everyday necessities is still challenging.